PERANCANGAN STRATEGIS SISTEM INFORMASI PEMINJAMAN RUANG FTI UKSW SALATIGA BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Adytia Luky Ivan Susanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Along with the development of the era there are several supporting factors that support the occurrence of changes from various aspects, one of which is Technology. The advent of this technology greatly helped human work in any case. All organizations and companies already use technology in carrying out their business processes and become a very important thing that must be owned or organization or company. Currently, the Faculty of Information Technology, Satya Wacana Salatiga Christian University is conducting a migration process to the space lending process, namely from the manual recording process to the web information system process. Because FTI UKSW Salatiga wants to utilize existing human resources and does not need a lot of human resources to serve all FTI students and outside FTI. To create a web information system requires a framework to support the Laravel framework. Laravel framework is very helpful because there are templates that have been provided so that programmers are faster in coding on a piece of work. The result of the design of this information system is in the form of a WEB application that can be controlled with the internet network. This WEB application makes it easy for FTI UKSW admins to input space data and borrower data quickly and efficiently.